PENGARUH TEMPERATUR SOLAR TERHADAP PERFORMA MESIN DIESEL DIRECK INJECTION PUTARAN KONSTAN - Murni, Murni (Diponegoro University, 2012)
The imperfect combustion process will be a problem in the development effort of diesel engine’s performance.Nonhomogen air–fuel mixing process is one of the factors which cause the imperfect combustion.By heating upthe diesel solar up to a certain temperature before it goes through the high pressure injection pump will lowerits density and viscosity. Therefore, when injected in the combustion chamber, it will formed smaller droplets offuel spray which result in a more homogenious air–fuel mixture. Also by using higher temperature will make thediesel fuel easier to ignite in order to compensate the limited time which is available in high speed operatingconditions. Diesel engine Dong Feng 1 cylinder direct injection at constant speed was used in this research. Thefuel used are solar with temperature variations in the range from 30oC to 70oC . The best thermal efficiency forsolar fuel is 30 % at 60oC with 28 % BSFC. In this condition, the fuel consumption was decreased 4 % bycomparing with that at 30oC.